Intelligent Traffic Information System for Klang Valley, Malaysia - Patrick Soh, Chin-Hooi; K. Radakrishnan, Kalaivani (2008)
The Klang Valley in Malaysia has been blessed with many roads and highways providing various alternative routes for motorists to choose to travel to their destinations. Nevertheless, motorists are not able to realize the full benefits of these alternative highways because they do not have real-time traffic information. This paper proposes a proof-of-concept open standard graphic system that could provide a bird-eye view graphically. The system could help drivers plan their routes and reduce traffic congestion. The graphical concept is applicable to other domains.